Рідкісні види в заплаві р. Сейм на території України - Козир, М.С. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
Сообщается о новых местонахождениях трех видов сосудистых растений: Dactylorhiza incarnata (L.) So, Gladiolus tenuis Bieb., Orchis palustris Jacq, занесенных во второе издание Красной книги Украины, и редком для Черниговской обл. виде Iris sibirica L. в пойме р. Сейм. Характеризуются местообитания видов, их ценотическая приуроченность, а также указывается численность популяций. New localities are reported for 3 species Dactylorhiza incarnata (L.) Soo, Gladiolus tenuis Bieb., Orchis palustris Jacq listed in the Red Data Book of Ukraine and also for localities of 1 rare species for Chernigiv region Iris sibirica L. in the valley of the Seim river. The habitats and caenotic features of all localities are characterised. Also strength populations characteristics for these species are provided.